A desterritorialização dos moradores do povoado Canela e a sua reterritorialização no espaço urbano de Palmas-TO - Moura, Pracidina Chaves (Universidade Federal do Tocantins, 2023)
This study was developed based on an analysis of socioterritorial phenomena carried out with the aim of analyzing the process of deterritorialization of the residents of village Canela and their reterritorialization in the urban space of Palmas-TO. Thus, this research plays a crucial role in documenting and analyzing the impacts of urbanization and deterritorialization on the respective traditional communities, increasing understanding of the challenges these people face, but also highlighting the importance of preserving cultural and territorial identities in a rapidly changing world. In addition, the research highlights the resilience and determination of this community in their struggle to maintain their roots and their history, despite the pressures of urbanization. Recognition of these struggles is essential for the promotion of fairer and more inclusive public policies that take into account the needs and rights of traditional communities in a context of continuous urbanization. The former residents of the village of Canela, who are now living in an urban space. The de-territorialization of the residents of the village of Canela, which was located on the right bank of the Tocantins River, was a traumatic process of forced displacement from a riverside community with a strong cultural identity to a distant urban area. This began with the construction of the Luís Eduardo Magalhães Hydroelectric Power Station, which flooded the old village and forced the residents to move to the city of Palmas-TO. After being relocated to Quadra 508 Norte, the residents faced difficulties adapting to a new way of life and preserving their cultural identity, as this forced change led to a loss of cultural identity and a move away from the community's traditional way of life. However, over time, they were reterritorialized in the urban space and managed to reorganize their activities and traditions, such as the celebration of the Divine Holy Spirit, so the community was reterritorializing itself and creating new bonds of identity with the city, preserving its culture and traditions in the midst of adapting to the urban environment. Public policies to preserve the cultural identity of the residents of Canela are important in this process of reterritorialization, which is why it should involve creating laws to protect cultural heritage, as well as carrying out studies to map and catalogue cultural expressions and encouraging the celebration of traditional festivals.